Unfolding perceptual continua - Albertazzi, Liliana (Advances in consciousness research ;, 2002)
The book analyses the differences between the mathematical interpretation and the phenomenological intuition of the continuum. The basic idea is that the continuity of the experience of space and time originates in phenomenic movement. The problem of consciousness and of the spaces of representation is related to the primary processes of perception. Conceived as an interplay between cognitive science, linguistics and philosophy, the book presents a conceptual framework based on a dynamic and experimental approach to the problem of the continuum. Besides presenting the primitives of a theory of.